PENGARUH CAPITAL STRUCTURE, GROWTH, SIZE, PROFITABILITY, & LIQUIDITAS TERHADAP NILAI PERUSAHAAN - Ernestine, Sherina; Sufiyati, Sufiyati (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This study aims to obtain empirical evidence regarding the effect of capital structure, growth, size, profitability, and liquidity on firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) period 2017-2020. This study used purposive sampling technique and obtained as many as 71 companies. The results of this study indicate that the capital structure proxied by DER and profitability as proxied by ROE has a positive and significant effect on firm value, size has a negative and significant effect on firm value. Growth has a positive and insignificant effect on firm value and liquidity as proxied by CR has a negative and insignificant effect on firm value